LNG and gas storage optimisation and valuation: Lessons from the integrated Irish and UK markets - Mel T. Devine; Marianna Russo (The Economic and Social Research Institute (ESRI), 2018)
To guarantee European countries with greater access to competitive energy sources, the European Union has identified new infrastructures for the achievement of a diversified, secure and affordable European single energy market. This paper aims to evaluate the impact on consumers' energy bill of new LNG and gas storage facilities. We focus on the integrated UK-Ireland gas system, which provides an interesting framework to assess socioeconomic benefits of new energy routes. We utilise a stochastic mixed complementarity problem model, which also incorporates stochastic gas supply cost and demand scenarios. Therefore, we assess the expected benefits for consumers of a diversified gas supply, and their sensitivity to changing market conditions. Our results imply the complementary of LNG and gas storage investments to manage shortterm peak loads and long-term seasonal loads and prices in gas markets. Nonetheless, economic benefits for consumers are dependent on market conditions. Overall, our results provide some suggestions on investments in new gas facilities, which are of interest to policy-makers and market participants.
Keywords: 330